The Relationship between Academic Programme Type and Student Satisfaction with the Quality of Higher Education in Uganda - Bagonza , Godfrey; Kaahwa, Yuda Taddeo (International Journal of African Higher Education, 2023)
This study examined the relationship between the type of academic programmes offered in Ugandan higher education institutions and student satisfaction with the quality of higher education. Highquality academic programmes are those that focus on the outcomes of the higher educational processes, including student retention and graduate destinations and employability, as well as expectations of earnings proportional to the qualification. Employing quantitative and qualitative research methods, the study analysed data gathered from 400 undergraduate students, six quality assurance directors, and 12 academic heads of departments in six Ugandan universities. It found that students in different academic disciplines and different universities believed that the academic programmes they selected were strongly related to their satisfaction with the quality of higher education.